Associations of the infancy body mass index peak with anthropometry and cardiometabolic risk in Mexican adolescents - Wei Perng; Jonggyu Baek; Christina W. Zhou; Alejandra Cantoral; Maria Martha Tellez-Rojo; Peter X. K. Song; Karen E. Peterson (Taylor & Francis Group, 2018)
Background: Early-life growth dynamics are associated with future health. Little is known regarding timing and magnitude of the infancy body mass index (BMI) peak with adiposity and metabolic biomarkers during adolescence. Aim: To examine associations of the infancy BMI peak with anthropometry and cardiometabolic risk during peripuberty. Methods: Among 163 ELEMENT participants, this study estimated age and magnitude of the infancy BMI peak from eight anthropometric measurements from birth-36 months using Newton's Growth Models, an acceleration-based process model. Associations were examined of the infancy milestones with anthropometry and cardiometabolic risk at 8-14 years using linear regression models that accounted for maternal calcium supplementation and age; child's birthweight, sex, and age; and the other infancy milestone. Results: Median age at the infancy BMI peak was 9.6 months, and median peak BMI was 16.5 kg/m2. Later age and larger magnitude of the peak predicted higher BMI z-score, waist circumference, and skinfold thicknesses; i.e. each 1 month of age at peak and each 1 kg/m2 of peak BMI corresponded with 0.04 (0.01-0.07) and 0.33 (0.17-0.48) units of higher BMI z-score, respectively. Later age at peak was also a determinant of worse glycaemia and higher blood pressure. Conclusion: Later age and larger magnitude of the infancy BMI peak are associated with higher adiposity at 8-14 years of age. Later age but not magnitude of the BMI peak are related to a worse cardiometabolic profile during peripuberty.